2011
DOI: 10.22610/imbr.v3i3.931
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Change on Employee Job Involvement: Mediating Role of Communication, Emotions and Psychological Contract

Abstract: The purpose of the current paper is to provide a conceptual framework for studying the impact of organizational change on employee job involvement while communication, emotions and psychological contract plays mediating role in this relationship. The current study conceptualize that organizational change followed by effective communication generate the positive emotions which ultimately increase the employee job involvement where as organizational change with ineffective communication causes negative emotions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…This study finding consisted with Sethi et al (2016) (7) on their study about job involvement among senior secondary school teachers they found that there was no significant gender difference in the job involvement of teachers. In addition the study conducted with Doobree (2009) (35) that there was no significant relationship between the (gender, age, educational qualifications and the length of service) of bank managers and their job involvement.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This study finding consisted with Sethi et al (2016) (7) on their study about job involvement among senior secondary school teachers they found that there was no significant gender difference in the job involvement of teachers. In addition the study conducted with Doobree (2009) (35) that there was no significant relationship between the (gender, age, educational qualifications and the length of service) of bank managers and their job involvement.…”
Section: Discussionsupporting
confidence: 71%
“…Job involvement is one's cognitive needs" fulfillment, which assists him or her to work harder and boost up his or her performance. Indeed, a higher degree of job involvement among the members of an organization is essential to enhance the organizational effectiveness (7) . There is a general consensus among researchers that employees with a high level of job involvement would place their jobs at the center of their overall interests (8) .On the other hand, employees with low levels of job involvement concentrate on other interests rather than their jobs (9) , and will be less creative and innovative (10) .…”
Section: Introductionmentioning
confidence: 99%
“…New change initiatives should prioritise the provision of coping mechanisms and support for those directly affected by the change that is introduced. This is also corroborated by Khalid and Rehman (2011), who assert that dealing with employees' feelings of discomfort and uncertainty, after http://www.sajip.co.za Open Access change implementation, creates feelings of appreciation among employees, and this can influence their levels of commitment to the change initiative.…”
Section: Discussionmentioning
confidence: 71%